The Existence of Yellow Books (Kitab Kuning) as the Sources of Islamic Studies at Islamic Boarding Schools Within the Industrial Revolution Dialectics - Ritonga, Mahyudin; Lahmi , Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
One pride of Islamic boarding schools in Indonesia is related to their curriculum. Although Indonesian government through the Ministry of Religious Affairs has organized the curriculum for educational institutions, kitab kuning still exist as a part of curriculum used at Islamic Boarding schools. Along with the rapid development of technology in the industrial revolution era 4.0, the existence of Kitab Kuning as the sources of Islamic studies seems to be seriously threatened. This article will explain the existence of Kitab Kuning as the main sources of Islamic studies in the industrial revolution era. This research used a qualitative method. The research data was collected through observation, interview, documentation, and focus group discussion. The data sources were the leaders, teachers, students, experts of Islamic boarding schools knowing a lot about the Kitab Kuning and industrial revolution demands. The research results showed that the Islamic Boarding School Students got difficulties and required more time to understand the meanings contained in those Kitab Kuning. The students also tended to open links containing Islamic sciences that changed the students’ habits from opening books to opening android, yet freedom of utilizing information technology is highly limited at the Islamic Boarding Schools in Indonesia.